Two Compact Cas9 Ortholog-Based Cytosine Base Editors Expand the DNA Targeting Scope and Applications In Vitro and In Vivo - Wu, Susu; Li, Liping; Li, Min; Sun, Shiyu; Zhao, Yuting; Xue, Xiaowen; Chen, Feiyu; Zhong, Jingli; Guo, Junfan; Qu, Qianhui; Wang, Xiongjun; Liu, Zhen; et al. (Frontiers in Cell and Developmental Biology, 2022)
CRISPR/Cas9-based base editing tools enable precise genomic installation and hold great promise for gene therapy, whereas the big size of Cas9 nucleases and its reliability on specific protospacer adjacent motif (PAM) sequences as well as target site preferences restrict the extensive applications of base editing tools. Here we generate two cytosine base editors (CBEs) by fusing cytidine deaminases with two compact codon-optimized Cas9 orthologs from Streptococcus_gordonii_str._Challis_substr._CH1 (ancSgo-BE4) and Streptococcus_thermophilus_LMG_18311 (ancSth1a-BE4), which are much smaller than Streptococcus pyogenes (SpCas9) and recognize NNAAAG and NHGYRAA PAM sequences respectively. Both CBEs display high activity, high fidelity, different editing window, and low byproducts for cytosine base editing with minimal DNA and RNA off-targeting activities in mammalian cells. Moreover, both editors show comparable or higher editing efficiencies when comparing with two engineered SpCas9 variants (SpCas9-NG and SpRY)-based CBEs in our tested target sites, which perfectly match the PAM sequences for ancSgo-BE4 or ancSth1a-BE4. In addition, we successfully generate two mouse models harboring clinically relevant mutations at Ar gene via ancSgo-BE4 and ancSth1a-BE4, which display androgen insensitivity syndrome and/or developmental lethality in founder mice. Thus, the two novel CBEs broaden the base editing toolkits with expanded targeting scope and window for efficient gene modification and applications.